2012
DOI: 10.1371/journal.ppat.1003003
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Cryptic Secondary Sigma Factor Gene Unveils Natural Competence for DNA Transformation in Staphylococcus aureus

Abstract: It has long been a question whether Staphylococcus aureus, a major human pathogen, is able to develop natural competence for transformation by DNA. We previously showed that a novel staphylococcal secondary sigma factor, SigH, was a likely key component for competence development, but the corresponding gene appeared to be cryptic as its expression could not be detected during growth under standard laboratory conditions. Here, we have uncovered two distinct mechanisms allowing activation of SigH production in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
133
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(135 citation statements)
references
References 88 publications
1
133
1
Order By: Relevance
“…Why pBS32 encodes a functional inhibitor of competence is unknown, but ComI may promote plasmid stability by excluding the uptake of competing plasmids. Many bacteria, including pathogens like Staphylococcus aureus, Streptococcus pyogenes, and Listeria monocytogenes, are nontransformable and yet carry genes which suggest that they could be capable of natural competence (50)(51)(52). Similarly, industrial strains such as Bacillus amyloliquefaciens, Bacillus licheniformis, Bacillus pumilus, and Bacillus subtilis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Why pBS32 encodes a functional inhibitor of competence is unknown, but ComI may promote plasmid stability by excluding the uptake of competing plasmids. Many bacteria, including pathogens like Staphylococcus aureus, Streptococcus pyogenes, and Listeria monocytogenes, are nontransformable and yet carry genes which suggest that they could be capable of natural competence (50)(51)(52). Similarly, industrial strains such as Bacillus amyloliquefaciens, Bacillus licheniformis, Bacillus pumilus, and Bacillus subtilis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Potential translation initiation codons (TTG) of sigH in S. aureus RN4220 were changed to Ochre stop codons (TAA) by using pMADt492 as described previously (21).…”
Section: Semiquantitative Reverse Transcription-pcr (Rt-pcr)mentioning
confidence: 99%
“…Among Gram-positive bacteria, two master regulators control the expression of competence-related genes: the transcription factor ComK (in B. subtilis) (18) and the alternative sigma factor H (in S. pneumoniae [19,20], S. aureus [21], and Lactobacillus sakei [31]). Rabinovich et al reported the presence of a ComK recognition site (the ComK box) upstream of the competence machinery operons (comG, comE, and comF) in L. monocytogenes (16).…”
Section: Canonicalmentioning
confidence: 99%
See 2 more Smart Citations